An environmental friendly leisure boat - Abd. Mukti, Mohd. Afifi; Tawi, Kamarul Baharin; Yaakob, Omar; Nasirudin, Ahmad; Abd. Ghani, Mohd. Pauzi; Mat Lazim, Tholudin (2006)
This paper presents a development of an environmental friendly leisure boat. The study seeks to choose appropriate hull form configuration to minimize bank erosion, propulsion system and material to prevent air and water pollution. An asymmetric catamaran hull form configuration was selected and an electric motor with solar cell system was chosen as propulsion systems. GRP material was chosen to get easy maintain and corrosive resistant.